2022
DOI: 10.1002/marc.202200114
|View full text |Cite
|
Sign up to set email alerts
|

Tough and Fatigue Resistant Cellulose Nanocrystal Stitched Ti3C2Tx MXene Films

Abstract: Ti 3 C 2 T x MXene (or "MXene" for simplicity) has gained noteworthy attention for its metal-like electrical conductivity and high electrochemical capacitance-a unique blend of properties attractive toward a wide range of applications such as energy storage, healthcare monitoring, and electromagnetic interference shielding. However, processing MXene architectures using conventional methods often deals with the presence of defects, voids, and isotropic flake arrangements, resulting in a trade-off in properties.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…The combination of MXene-silk also exhibited enhanced cell-viability of up to ≈200% at 10% silk, providing an important insight into the potential use of MXene fibers in biomedical applications. Although other nanomaterial fillers such as nanocellulose [46,52] and graphene oxide [27] were also reported to result in higher mechanical properties, biocompatibility varies with every material. Thus, subsequent cytotoxicity testing after material fabrication is highly recommended.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of MXene-silk also exhibited enhanced cell-viability of up to ≈200% at 10% silk, providing an important insight into the potential use of MXene fibers in biomedical applications. Although other nanomaterial fillers such as nanocellulose [46,52] and graphene oxide [27] were also reported to result in higher mechanical properties, biocompatibility varies with every material. Thus, subsequent cytotoxicity testing after material fabrication is highly recommended.…”
Section: Discussionmentioning
confidence: 99%
“…[76] For example, it has been found that Ca 2 + was used in the MXene/nanocellulose suspension during the filtration process as a bridging and cross-linking agent to improve the toughness of the MXene/nanocellulose composite film electrode. [77] The introduction of Ca 2 + caused a significant increase in the tensile strength (~285 MPa) and breaking energy (~16.1 MJ/m 3 ). [77] Although the toughness of MXene/nanocellulose was enhanced, the use of Ca 2 + in MXene/nanocellulose suspension decreased the interlayer spaces than the individual MXene/nanocellulose composites, from 1.32 nm to 1.25 nm respectively, which caused a very slight reduction of capacitive performance, from ~990 F/cm 3 to 920 F/cm 3 .…”
Section: Cross-linkingmentioning
confidence: 99%
“…[77] The introduction of Ca 2 + caused a significant increase in the tensile strength (~285 MPa) and breaking energy (~16.1 MJ/m 3 ). [77] Although the toughness of MXene/nanocellulose was enhanced, the use of Ca 2 + in MXene/nanocellulose suspension decreased the interlayer spaces than the individual MXene/nanocellulose composites, from 1.32 nm to 1.25 nm respectively, which caused a very slight reduction of capacitive performance, from ~990 F/cm 3 to 920 F/cm 3 . [77]…”
Section: Cross-linkingmentioning
confidence: 99%
“…The atomic force microscope (AFM) (figure 1(a)) and scanning electron microscope (SEM) images (figures S1(b) and (c)) showed that MAX powders were successfully exfoliated into MXene sheets ∼2 nm thick and ∼0.5-1.5 µm wide, while commercial CNCs were found to be ∼150 nm long and ∼5 nm in diameter (figure 1(a)). When the two aqueous dispersions (MXene and CNC) were physically mixed, MXene formed a network of interconnected sheets bridged by CNC [17,29], resulting in an apparent shift in hydrodynamic diameter of MXene and CNC from ∼1000 nm and ∼150 nm, respectively to ∼1500 nm for the mixed system (figures 1(a) and (b)).…”
Section: Characterization Of Mxene Cnc and Mxene-cnc Dispersionsmentioning
confidence: 99%
“…Recently, a stepwise strategy of introducing bridging agents followed by cross-linkers into MXene structures, known as sequential-bridging (SB) [27,28], demonstrated simultaneous improvement in sheet adhesion and alignment, without loss of electrical contact or causing undesirable aggregation. SB MXene (SBM) production typically starts with a bridging step, performed by functionalizing the MXene sheet surface using H-bonding rich polymers or nanomaterials such as alginate [21], polydopamine (PDOPA) [16], cellulose nanocrystals (CNCs) [17,29] and carboxymethyl cellulose (CMC) [20] before processing into architectures. Fortification is then undertaken by infiltrating the bridged-MXene architecture with cross-linkers such as Ca 2+ [16] or borate ions [20], in order to simultaneously enhance inter-nanomaterial adhesion and lower d-spacing to regain electrical contact [16,20,21].…”
Section: Introductionmentioning
confidence: 99%